Helmet use among motorcyclists: observational study in the city of Mar del Plata, Argentina Uso do capacete por motociclistas: estudo observacional na cidade de Mar del Plata, Argentina - Rubén Daniel Ledesma; Raquel Inés Peltzer (Universidade de São Paulo, 2008)
The objective of the study was to assess the use of helmets in a community where helmet use is mandatory but low as there is no police enforcement. A sample comprising 451 motorcyclists in the city of Mar del Plata, Argentina, was studied in 2006. The following variables were studied: gender, type of motorcycle, weather conditions, time of the day, city area and type of road where motorcyclists traveled. Data were analyzed through a multiple logistic regression model. An overall 40% prevalence (95% CI: 35.5;44.5) of helmet use was found. Higher rates of helmet use were seen among women, and under unfavorable weather conditions, lower rates were found in the city outskirts, and variable use was seen according to the type of motorcycle. There is a need to improve law enforcement and to promote education of motorcyclists. O estudo teve por objetivo analisar o uso de capacetes em uma comunidade onde, embora o uso seja obrigatório, não há policiamento e o uso é baixo. A amostra foi composta por 451 motociclistas observados na cidade de Mar del Plata, Argentina, em 2006. As variáveis estudadas foram: sexo do motociclista, tipo de motocicleta, condições climáticas, hora do dia, região da cidade e tipo de via em que circulavam as motocicletas.Os dados foram analisados em modelo de regressão logística múltipla. A prevalência do uso do capacete foi de 40% (IC 95%: 35,5;44,5), com maior uso pelas mulheres e em condições climáticas desfavoráveis, menor uso na periferia da cidade e variações segundo o tipo de motocicleta. Os resultados mostram a necessidade de haver maior controle e melhor educação dos condutores motociclistas.